2019
DOI: 10.1136/archdischild-2019-316918
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for European paediatric emergency medicine

Abstract: ObjectiveResearch in European Paediatric Emergency Medicine (REPEM) network is a collaborative group of 69 paediatric emergency medicine (PEM) physicians from 20 countries in Europe, initiated in 2006. To further improve paediatric emergency care in Europe, the aim of this study was to define research priorities for PEM in Europe to guide the development of future research projects.Design and SettingWe carried out an online survey in a modified three-stage Delphi study. Eligible participants were members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
1
26
0
2
Order By: Relevance
“…Even though most participating centres mentioned that their guidelines were based on the NICE guideline, in the process of translation from the UK to another setting, the evidence probably is weighed according to the local setting and practice. This may induce further practice variation across centres [18].…”
Section: Interpretation and Comparison To Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Even though most participating centres mentioned that their guidelines were based on the NICE guideline, in the process of translation from the UK to another setting, the evidence probably is weighed according to the local setting and practice. This may induce further practice variation across centres [18].…”
Section: Interpretation and Comparison To Existing Literaturementioning
confidence: 99%
“…Future research should focus on identifying reasons for noncompliance, including cultural and healthcare factors at the individual, organizational and national level [18]. Qualitative research could provide more in-depth information on the reasons for the observed discrepancies in vital sign measurements across Europe.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Delphi process is a formalised method for obtaining consensus, whereby participants respond to successive questionnaires that aim to identify common principles or proposals 9 10. It is used for multiple purposes, including determining common priorities for research 11–14. Responses are qualitative (free text comments) and quantitative (assigning ranks/scores).…”
Section: Methodsmentioning
confidence: 99%
“…This need is well recognized by pediatric emergency medicine physicians; a recent survey conducted by the Research in European Paediatric Emergency Medicine network found that fever and risk stratification are research priorities. 6 Lillitos and colleagues assessed the performance of the Brighton and Children's Observation and Severity Tool (COAST) pediatric early warning scores to predict serious medical and surgical illness and requirement for hospital admission in pediatric patients presenting to the emergency department. 7 A high score was specific but not sensitive for predicting the need for hospital admission and serious medical illness, and performed poorly at predicting serious surgical illness.…”
mentioning
confidence: 99%